Roles of the structural defects and the combined acidity of H3PW12O40/Zr-MCM-41 catalysts in ultralow sulfur diesel production. (10th January 2022) - Chen, Lifang; Wang, Jin An; de la Fuente, Natali; Zhou, Sinong; Jiang, Peng; Song, Yueqin; Zhou, Xiaolong
Abstract : This work contributes to the production of ultralow-sulfur diesel using phosphotungstic acid immobilized on Zr-MCM-41 catalysts containing structural defects and combined acidity. Abstract : Oxidative desulfurization (ODS) has been become an important technical route for the production of ultralow-sulfur fuel. This work focuses on a deep understanding of the roles of structural defects, surface acidity and catalytic properties of phosphotungstic acid grafted on Zr-doped MCM-41 catalysts in the oxidation of 4, 6-dimethyldibenzothiophene (4, 6-DMDBT) in a model diesel. Two kinds of Zr-MCM-41 mesoporous solids (termed ZrM-I and ZrM-II) were synthesized with different methods and their structural defects and surface acidity were investigated. When H3 PW12 O40 (termed HPW) was grafted on the ZrM solids, their dispersion and structural deformation were largely governed by the interaction with the ZrM support. Three types of HPW nanoparticles, confirmed by 31 P-NMR-MAS spectra, were formed, which were related to the unchanged, deformed and defective Keggin units. The amount of total surface acidity was 227 μmol g −1 for HPW/ZrM-I and 307 μmol g −1 for the HPW/ZrM-II catalyst. For 4, 6-DMDBT oxidation, the pore regularity and structural defects of the ZrM supports and the surface acidity of the HPW/ZrM catalysts played the key roles. The HPW/ZrM-II catalyst showed higher catalytic activity, due to its larger number of surface acid sites resulting from the greater amount of deformed and defective Keggin-type nanoclusters. The 4, 6-DMDBT conversion reached nearly 100% over the HPW/ZrM-II catalyst under optimal condition (reaction temperature: 70 °C; reaction time: 60 min; catalyst concentration: 0.3 g L −1 ; H2 O2 /4, 6-DMDBT molar ratio: 8; HCOOH/H2 O2 molar ratio: 1.5). The 4, 6-DMDBT oxidation was sterically favored on the combined Lewis (L) and Brønsted (B) acid sites in the catalysts. L acid sites were the centers for 4, 6-DMDBT adsorption and the neighboring B acid sites participated in the transfer of protons and oxygen atoms between adsorbed sulfur compounds and the surface peroxophosphotungstate complex, benefiting the 4, 6-DMDBT oxidation.